Respuesta :

Answer:

The correct answer would be [tex]a=\sqrt{c^2-b^2}[/tex]

Step-by-step explanation:

given [tex]a^2+b^2=c^2[/tex] we want to solve for a

How?

We can do this by using basic algebra ( isolating the variable (a ))

Step 1 subtract [tex]b^2[/tex] from each side

[tex]a^2+b^2-b^2=a^2\\c^2-b^2=c^2-b^2[/tex]

now we have [tex]a^2=c^2-b^2[/tex]

step 2 take the square root of each side

[tex]\sqrt{a^2} =a\\\sqrt{c^2-b^2} =\sqrt{c^2-b^2}[/tex]

we're left with [tex]a=\sqrt{c^2-b^2}[/tex]

Hence your answer is A

ACCESS MORE